The Estimation of Body Weight in Aceh Cattle using some Body Dimension - W.P. B. Putra; . Sumadi; T. Hartatik (Jurnal Ilmu dan Teknologi Peternakan, 2014)
This study aims to find the best estimation of body weight (BW) of Aceh cattle (three year ages) by body dimensions: hearth girth (HG), body length (BL) and width height (WH) in Aceh cattle at BPTU-HPT Sapi Aceh Indrapuri. The materials in this research were 79 adults Aceh cattle (three years old) which consisted of 40 female cattle and 39 male cattle. The results showed that the regression formula for adult male cattle were BW = 2.50 (HG) + 0.19 (BL) + 0.18 (WH) – 197.89 and for adult female cattle were BW = 1.43 (HG) + 1.51 (BL) + 0.15 (WH) – 195.42. The correlation coefficient value (r) of three body size to BW in adult male-female cattle were 0.94 and 0.86 respectively. The determination coefficient value (R2) in their formula were 0.88 (male)  and 0.74 (female). The adult weight of Aceh cattle could be explain by HG, BL and WH as + 80 % (male) and + 70 % (female), and the otherwise from the unknown factor in out regression model.